2005
DOI: 10.1111/j.1540-8167.2005.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dominant Prolongation of the Filtered QRS Duration in the Right Precordial Leads and Clinical Characteristics in Brugada Syndrome

Abstract: The dominant prolongation of the filtered QRS duration in the right precordial leads may be related to the risk of arrhythmic event in Brugada syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…The presence of late potentials and prolonged filtered QRS duration on signal-averaged ECG also have been linked to arrhythmic risk in Brugada syndrome. 26,27 Increased QRS fragmentation recently was shown to be related to the incidence of arrhythmic events in Brugada syndrome. 28 A mechanism explaining the Brugada ECG type solely by RVOT conduction delay has been proposed (see Figure 3 in Meregalli et al 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of late potentials and prolonged filtered QRS duration on signal-averaged ECG also have been linked to arrhythmic risk in Brugada syndrome. 26,27 Increased QRS fragmentation recently was shown to be related to the incidence of arrhythmic events in Brugada syndrome. 28 A mechanism explaining the Brugada ECG type solely by RVOT conduction delay has been proposed (see Figure 3 in Meregalli et al 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 We previously reported that dominant prolongation of the filtered QRS duration in the right precordial leads was related to the risk of arrhythmic events in BS and that these parameters were not related to the conduction time from the RVOT to the RVA or to the HV interval. 4 We postulated that the prolongation of RfQRSd was a different parameter from conduction delay, including the HV interval, and we reported that the last part of the delayed potential with fQRSd in the right precordial leads was a low-frequency component compared with the LP in patients with ARVC. 5 Moreover, we reported a discrete LP in SAECG related to coved ST elevation, and this potential was induced by pilsicainide and abolished by quinidine when the ECG showed a coved-type ST elevation.…”
Section: Prolongation Of St-qrs During Premature Stimulationmentioning
confidence: 98%
“…The standard precordial leads, V1-6, were amplified, digitized, and averaged (200-300 beats/min), and the fQRSd was measured. 4 The fQRSd in leads V2 and V5 was defined as the RfQRSd and LfQRSd, respectively. 4…”
Section: Saecgmentioning
confidence: 99%
See 1 more Smart Citation
“…This may subsequently help in risk stratification of arrhythmic events in this group of people. Previous reports examined HRV [10][11][12][13] and ventricular LPs [14][15][16][17][18][19] in patients with Brugada syndrome (which is also an ECG phenotype characterized by elevated ST segment), but limited data exist on the association between early repolarization and these markers of arrhythmogenesis.…”
Section: Introductionmentioning
confidence: 97%